1998
DOI: 10.1038/nbt0998-839
|View full text |Cite|
|
Sign up to set email alerts
|

Agrobacterium tumefaciens-mediated transformation of filamentous fungi

Abstract: Agrobacterium tumefaciens transfers part of its Ti plasmid, the T-DNA, to plant cells during tumorigenesis. It is routinely used for the genetic modification of a wide range of plant species. We report that A. tumefaciens can also transfer its T-DNA efficiently to the filamentous fungus Aspergillus awamori, demonstrating DNA transfer between a prokaryote and a filamentous fungus. We transformed both protoplasts and conidia with frequencies that were improved up to 600-fold as compared with conventional techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
497
3
20

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 790 publications
(552 citation statements)
references
References 21 publications
18
497
3
20
Order By: Relevance
“…T-DNA tagging has been used successfully to find new genes [30,70] and T-DNA tagging projects on fungi have recently been initiated in many laboratories around the world [31,68]. AMT is very suitable for insertional mutagenesis as it can cause a relatively high frequency of transformation [71][72][73] and often creates single-copy integrations [27,31]. Also, T-DNA appears to integrate approximately at random [31,73], although integration may be targeted towards transcribed regions [70,74] and promoters in particular [70].…”
Section: T-dna Taggingmentioning
confidence: 99%
See 1 more Smart Citation
“…T-DNA tagging has been used successfully to find new genes [30,70] and T-DNA tagging projects on fungi have recently been initiated in many laboratories around the world [31,68]. AMT is very suitable for insertional mutagenesis as it can cause a relatively high frequency of transformation [71][72][73] and often creates single-copy integrations [27,31]. Also, T-DNA appears to integrate approximately at random [31,73], although integration may be targeted towards transcribed regions [70,74] and promoters in particular [70].…”
Section: T-dna Taggingmentioning
confidence: 99%
“…AMT appears to be relatively efficient, often leading to a high frequency of gene targeting mediated by fungal recombination/repair proteins [100,101]. The generally higher frequency of recombination achieved by AMT may be due to the fact that the T-DNA is linear and single-stranded, a preferred substrate for homologous recombination [72,102], and is accompanied by Agrobacterium proteins that specifically interact with DNA-associated proteins in the recipient cell [74]. Electroporation, has also been used successfully for gene targeting although the frequency of homologous recombination is lower than AMT [2,103].…”
Section: Targeted Gene Disruption/replacementmentioning
confidence: 99%
“…The cells were grown for 5 h before A. tumefaciens and H. cylindrosporum were cocultivated as follows: 100 μl of bacterial culture (∼1×10 3 bacteria) was added to each glass microfibre disc containing macerated fungal mycelium. Discs were placed on cocultivation medium (De Groot et al 1998) (l −1 : 5 g KH 2 PO 4 ; 2.5 g (NH 4 ) 2 SO 4 ; 0.5 g CaCl 2 2H 2 O; 1.5 g MgSO 4 7H 2 O; 0.25 g NaCl; 0.01 mg thiamine-HCl; 2 g glucose; 10 mg FeCl 3 ; 0.5% glycerol; 40 mM MES-KOH pH 5.3) supplemented with 200 μM acetosyringone. The plates were incubated at 23°C for 96 h. After cocultivation, glass microfibre discs were transferred to YMG medium supplemented with 200 μM claforan (Aventis, Germany) to counter select Agrobacterium cells and 100 μg ml −1 hygromycin B to select for fungal transformants.…”
Section: Agrobacterium Tumefaciens-mediated Transformationmentioning
confidence: 99%
“…In this study, all the transformation experiments were carried out according to the previously described protocol unless otherwise noted. 21) Initially, binary vector pBI-hph, having the hph gene as selection marker, was introduced into A. tumefaciens LBA4404 by electroporation. 30) The transformants were isolated on YEB agar plates supplemented with Rif (50 mg/mL), Str (20 mg/mL), and Kan (50 mg/mL), and confirmed by PCR and enzyme digestion.…”
Section: Methodsmentioning
confidence: 99%
“…It can be used to achieve targeted gene disruption and random insertional mutation. Since de Groot et al 21) reported that ATMT can be used for the transformation of filamentous fungi, it has been considered to be more convenient, stable, and efficient than traditional transformation methods used in fungi. Reports on ATMT indicate that the transformation efficiency of filamentous fungi via A. tumefaciens is about 300-9,000 transformants per 10 7 spores, which was improved up to 600-fold as compared to results for PEG transformation of protoplasts.…”
mentioning
confidence: 99%